Inteligência emocional como fator protetor do burnout em professores do 2. º e 3. º Ciclos e Secundário da RAM - Andrade, Cláudia (2014)
Emotional intelligence is the ability to perceive, use, understand and regulate emotions to facil itate thought (Mayer and Salovey, 1997). The concept of burnout is the English expression to describe what stopped functioning because of the exhaustion of energy (France, 1987, cited by Carlotto, 2012).This study aimed to understand the perceived emotional intelligence as a protective factor against burnout, as well as studying the relationship between emotional intelligence and burnout. The sample was constituted by 250 teachers in the 2nd cycle (26.4%), 3rd cycle (57.2%) and Secondary school (16.4%), with (70.4%) females and (29.6%), males in the Autonomous Region of Madeira (RAM), Portugal. As instruments, we used a socio-demographic and professional’s questionnaire, the trait meta mood scale (TMMS-24), the expressiveness and emotion regulation of Berkeley questionnaire and the Maslach burnout inventory (MBI). In the study did not find evidence that marital status, age, length of service and level of educa tion influences taught emotional intelligence and burnout. Only gender seems to influence emotion al intelligence. To confirm the statistical relationship between emotional intelligence and burnout, we used Spearman´s correlation test between variables and it was concluded that the higher the repair of emotions, the less emotional exhaustion and depersonalization and higher the revaluation emotions are higher is the emotional exhaustion.